Impact of an Educational Intervention on Hygiene Knowledge and Practices Among Municipal Waste and Sanitation Workers in Nelson Mandela Bay, South Africa - Alive Ntunja; Wilma ten-Ham Baloyi; June Teare; Oyedele Opeoluwa; Paula Melariri (Advances in Public Health)
Safe and clean environments in the urban and peri-urban settlements depend on municipal waste and sanitation workers (MWSWs). They accomplish this by performing tasks such as sweeping streets, collecting domestic waste regularly, pit latrine cleaning, cleaning public toilets, and operating waste collection trucks. However, due to a lack of hygiene education, their hygiene knowledge and practices are poor. The study investigates how an educational intervention impacts hygiene knowledge and practices among MWSW in the study area. The study used a quasi-experimental study (pre- and post-test) design. Data was collected from 201 conveniently sampled MWSW using a self-administered structured questionnaire. The collected data was captured in a QuestionPro survey platform and analysed in Microsoft Office 365 (Microsoft Excel; 2019 version) and R software (version 4.4.1). An educational intervention based on existing literature was implemented. Inferential and descriptive statistics were used to analyse and describe the data. Participants comprised of 73.6% males and 26.4% females. The study participants had poor hygiene knowledge and practices prior to the educational intervention. Based on the paired samples t-test, there was a significant difference post-intervention phase in the mean scores for hygiene knowledge of 4.0 (±4.8), p<0.001, as well as hygiene practice scores of 4.3 (±3.4), p<0.001. The educational programme has significantly improved MWSW hygiene knowledge and practices. The ongoing implementation of similar initiatives is highly recommended amongst MWSWs, thus, preventing hygiene-related infections amongst the studied population and fostering a healthier environment.